2013
DOI: 10.1097/sap.0b013e31824680a9
|View full text |Cite
|
Sign up to set email alerts
|

Histological Changes of the Voice Tube and Possible Clinical Consequences After Voice Reconstruction With Free Ileocolon Flap

Abstract: Free ileocolon flap has become a valid option for restoration of speech after pharyngolaryngectomy. After transfer, deprivation of the trophic intestinal contents and exposure to chronic intermittent airflow could substantially modify the structure of the voice tube, compromising its function. Biopsy specimens from 14 voice tube segments were examined. Sections were evaluated after staining with hematoxylin-eosin, trichromic Masson, and antiproliferating cell nuclear antigen. In all samples, the mucosa display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…For these reasons, rapid autolysis is initiated soon after the onset of ischemia. Microstructural changes are noted even within 30 min of ischemia . If the ischemia time is too long, the bowel segment will not survive even after optimal microvascular anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, rapid autolysis is initiated soon after the onset of ischemia. Microstructural changes are noted even within 30 min of ischemia . If the ischemia time is too long, the bowel segment will not survive even after optimal microvascular anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies reported the use of postoperative chemotherapy or radiotherapy (►Table 3). 12,13,15,[17][18][19][20][24][25][26][27][28][29]33,[35][36][37][38][39] Primary and secondary reconstructions were performed in 24.6 (n ¼ 134) and in 19.1% (n ¼ 104) of the cases, respectively (►Table 4). The surgical time ranged from 8 to 14.5 hours reported in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…5 In the last decade, our group has conducted a significant number of aerodigestive track reconstructions using free and pedicle bowel flaps. 8,12,13,[18][19][20] Even though the success rate of these flaps is high, 6 we have noticed that when a ischemic event occurs, the portion of the bowel conduit that survives is usually the one not covered by serosa (e.g., posterior wall of the terminal ileum and ascending colon). However, and up to now, no study has demonstrated this physiological process among bowel conduits with and without serosa during ischemic events.…”
Section: Discussionmentioning
confidence: 99%
“…Free tissue transfer based on bowel conduits for pharyngolaryngectomy reconstruction has been used for many years with very promising outcomes. 10,14,15,19 From the clinical standpoint and based on many years of clinical observation by the senior author, 3,5,8,11,12,18,19 the physiological response of some of these bowel conduits during ischemic events is different. The lack of serosa in the posterior aspect of the ileum and colon compared with an intact serosal layer throughout the circumference of the jejunum is a possible hypothesis for the difference in behavior of these conduits during a period of ischemic/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation